MEWUJUDKAN EKONOMI MANDIRI MELALUI PENDIDIKAN ENTREPRENEUR ALA NABI MUHAMMAD - Kholifah, Ni'matul; Taufikurrahman, Taufikurrahman (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2019)
This paper is a study based on a literature study with the theme raised is realizing an independent economy through the education of entrepreneurs the style of the Prophet Muhammad. Indonesia with the largest Muslim population in the world has great potential to produce superior Muslim entrepreneurs in order to achieve an economic independence, this Muslim entrepreneur will run his business in accordance with the Islamic economic concept which prohibits ribawi cases and makes falah as the goal of every activity undertaken. . There are two important questions in this first papper, What is the design of entrepreneur education in Indonesia? Second, how is the education of entrepreneur Muhammad ala Muhammad? By using a content analysis approach to explain the concept of entrepreneur education in the style of the Prophet Muhammad. The results of this paper are the first to know the design of entrepreneurship education in Indonesia, the second to know the entrepreneur education style of the Prophet Muhammad.